Understanding Non-Suicidal Self-Injury: Qualitative Study of a Complex Phenomena - Lusi Nur Ardhiani; Sofia Retnowati (International Journal Labs, 2022)
The high incidence of non-suicidal self-injury becomes a need to be understood. Self-injury needs to get serious attention because the cases were increasing every year and can cause death even though there was no intention to commit suicide. The aims of the study were to build a deep understanding of participant’s experiences in doing self-injury and after stopping the behavior. This study is a qualitative study of Phenomenology, with a self-injury survivor as the participant. This research has gained ethical clearance and produced interview data which were then analyzed with Interpretative Phenomenological Analysis (IPA). The interview emerged seven key themes related to self-injury including interpersonal relationships as trigger, uncontrolled urge, form of emotions regulation, a way to communicate, self-injury changes, positive coping strategies affect the reduction, and positive interpersonal relationships reduced self-injury. This study showed that the emergence of self-injury was strongly influenced by negative interpersonal relations. Repetitions of self-injury were formed due to the uncontrolled urge and the lack of positive strategies that can provide the same satisfaction. Environment’s support and acceptance can be the main keys to reduce self-injury. In addition, non-destructive coping strategies to express negative emotions needs to be taught and socialized from early age.